Relationships between running economy and temporal EMG characteristics of bi-articular leg muscles - Heise, G. D.; Morgan, D. W.; Hough, H.; Craib, M. (International Journal of Sports Medicine, 1996)
Relationships between running economy (RE; submaximal VO(2) for a given running speed) and the temporal EMG characteristics of bi-articular leg muscles were quantified in a group of well-trained runners. Nine subjects completed three test sessions: a determination of maximal aerobic demand (VO(2)max); an accommodation session at the experimental speed of 4.13 m.s(-1) and a session during which EMG and RE data were collected simultaneously at the experimental speed of 4.13 m.s(-1) Measures of muscle onset, on-time durations, and on-time coactivation durations were calculated from the following muscles: rectus femoris, medial hamstrings, lateral hamstrings, and gastrocnemius. Nonparametric correlations between RE and EMG characteristics displayed both positive and negative relationships and exhibited a wide range of values. Two EMG measures were significantly correlated (r > 0.67) with RE. Earlier onset of rectus femoris during swing phase and a shorter duration of hamstring - gastrocnemius coactivation during swing were associated with more economical runners. Although not statistically significant, correlation coefficients calculated for measures of coactivation during stance and RE ranged from -0.42 to -0.65. This trend indicates that individuals who exhibited a greater amount of coactivation between bi-articular muscles during the stance phase of the running cycle tended to be more economical. These relationships suggest different activation patterns in bi-articular muscles between economical and uneconomical runners.